2004
DOI: 10.1126/science.1101312
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Expression Map for the Euchromatic Genome ofDrosophila melanogaster

Abstract: We used a maskless photolithography method to produce DNA oligonucleotide microarrays with unique probe sequences tiled throughout the genome of Drosophila melanogaster and across predicted splice junctions. RNA expression of protein coding and nonprotein coding sequences was determined for each major stage of the life cycle, including adult males and females. We detected transcriptional activity for 93% of annotated genes and RNA expression for 41% of the probes in intronic and intergenic sequences. Compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
205
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(219 citation statements)
references
References 28 publications
8
205
0
2
Order By: Relevance
“…This stronger net selection may reflect a direct increase in the strength of selection active on adult reproductive success relative to juvenile viability (adult mortality is very low in the IV population), or may be caused by a larger number of adultspecific segregating mutations. Very few transcripts in D. melanogaster appear to be adult specific (Arbeitman et al, 2002), and most genes in this organism appear to be developmentally regulated (Stolc et al, 2004), which suggests that for the majority of genes the opportunity for selection exists across the entire life history. As the total inbreeding load appears to be dominated by the reproductive success of adults, we expect that a reduction in the numbers of mutations affecting adult female fitness as a result of sexual selection would also result in a meaningful increase in their mean fitness.…”
Section: Inbreeding Load Across Life Historymentioning
confidence: 99%
“…This stronger net selection may reflect a direct increase in the strength of selection active on adult reproductive success relative to juvenile viability (adult mortality is very low in the IV population), or may be caused by a larger number of adultspecific segregating mutations. Very few transcripts in D. melanogaster appear to be adult specific (Arbeitman et al, 2002), and most genes in this organism appear to be developmentally regulated (Stolc et al, 2004), which suggests that for the majority of genes the opportunity for selection exists across the entire life history. As the total inbreeding load appears to be dominated by the reproductive success of adults, we expect that a reduction in the numbers of mutations affecting adult female fitness as a result of sexual selection would also result in a meaningful increase in their mean fitness.…”
Section: Inbreeding Load Across Life Historymentioning
confidence: 99%
“…A genome-wide comparison of Dmel-Dpse synteny blocks to changes in gene expression throughout the Dmel life cycle suggested that microsynteny is preserved at some loci in order to maintain coregulation of neighboring genes (Stolc et al 2004; see also erratum at http://bussemaker.bio.columbia.edu/ papers/Science2004/). Figure 4 shows two loci that are likely to be under dual pressures to maintain HCNE arrays and coregulated genes.…”
Section: Hcne Arrays Mark Regulatory Domains Maintained In Evolutionmentioning
confidence: 99%
“…Of particular interest is what factors affect the rate of expression divergence between duplicate genes? This question has not been well explored, although some factors such as developmental constraint have been investigated [10,15,16]. Because environmental factors such as abiotic and biotic stresses tend to change faster than internal factors such as developmental programs, we hypothesize that environmental factors accelerate expression divergence between duplicate genes.…”
Section: Introductionmentioning
confidence: 99%